(untitled) (e-Journal of Linguistics, 2023)
This research purposed to find out the student’s reading comprehension by the types of eco-descriptive texts to increase student’s English reading skills at senior high school 1 Maronge. The method of this research of this research applied quasi-experimental research The sampling technique used cluster random sampling technique, which the total sample of this research is 63 students. Data collection techniques used are observation and testing. In addition, the test implemented the pre-test and post-test design. Techniques for analyzing data used descriptive statistical tests and paired sample t- tests. Furthermore, The results of the sample paired t-test showed that the sig. (2-tailed) which is 0.000, the df value is 230, the tcount value is -59.786 which has a positive meaning of 59.786, and the mean value of paired differences is -36.801. So, it can be concluded that sig. (2-tailed) is 0.000 <0.05, and tcount -59.786 > ttable 1.653. This means that there is a significant effect on the use of Eco-Descriptive Text to Increase Students’ English Reading through posttest and pretest.